Assessment of quality of life after upper extremity transplantation: Framework for patient-reported outcome scale domains - Tyner, Callie E.; Slotkin, Jerry; Kisala, Pamela A.; Levin, L. Scott; Tintle, Scott M.; Tulsky, David S. (Frontiers in Psychology, 2023)
Upper extremity transplantation offers the promise of restored function and regained quality of life (QOL) for individuals who have sustained hand or arm amputation. However, a major challenge for this procedure becoming an accessible treatment option for patients is the lack of standard measures to document benefits to QOL. Patient-reported outcomes (PRO) measures are well-suited for this kind of intervention, where the perspective of the patient is central to defining treatment success. To date, qualitative work with experts, clinicians, and patients has been used to identify the most important domains of QOL for PRO item development. Specifically, our group’s qualitative work has identified several domains of QOL that are unique to individuals who have received upper extremity transplants, which are distinct from topics covered by existing PRO measures. These include emotional and social aspects of upper extremity transplant, such as Expectations and Perceived Outcomes, Integration and Assimilation of Transplant, Fitting in, and Post-Surgical Challenges and Complications. The broad topic of Satisfaction with Transplant was subdivided into three subtopics: Function, Sensation, and Aesthetics. Satisfaction with Sensation was also identified as a unique domain not evaluated by existing PRO measures. This report operationalizes these eight QOL domains by presenting scoping definitions. This manuscript describes the work that has been completed for domain characterization as an early step toward developing standardized PRO measures to evaluate these important outcomes specific to upper extremity transplantation.